Identity discourse and phenomenon of reunion on West Sumatran student - Wirman, Welly; Marta, Rustono; Sari, Genny Gustina; Azahari, Helmi; Hadisty, Hadisty (Faculty of Communications Science, Dr. Soetomo University, 2022)
This study aims to determine the goals, motives, and discourses on the identity of the West Sumatra overseas student reunion participants in Pekanbaru. Reunions have become popular and seem to be a way of life in our society. Communicative Action Theory will be used to identify a reunion between a school in Pekanbaru. This study uses a qualitative research method with a phenomenological approach. The results showed that the meaning of reunion was divided into three, namely the meaning of the purpose of silaturrahmi, the The motives are divided into the Bacarito Lamak motive, the fierce motive, and the Kepo motive. Furthermore, in the context of motifs consisting of motifs while diving, drinking water motives and motives provide greater benefits in the form of discussion motives and social motives. Identity discourse consists of appearance, self-actualisation, and connectivity rather than a show-off.